2023
DOI: 10.1111/pce.14711
|View full text |Cite|
|
Sign up to set email alerts
|

Increased activity of core photorespiratory enzymes and CO2 transfer conductances are associated with higher and more optimal photosynthetic rates under elevated temperatures in the extremophile Rhazya stricta

Luke M. Gregory,
Ludmila V. Roze,
Berkley J. Walker

Abstract: Increase photorespiration and optimising intrinsic water use efficiency are unique challenges to photosynthetic carbon fixation at elevated temperatures. To determine how plants can adapt to facilitate high rates of photorespiration at elevated temperatures while also maintaining water‐use efficiency, we performed in‐depth gas exchange and biochemical assays of the C3 extremophile, Rhazya stricta. These results demonstrate that R. stricta supports higher rates of photorespiration under elevated temperatures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 82 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…First, V cmax , J max , and A max data were collected in the field using a LI-6800 Portable Photosynthesis System (Licor Bioscience, Lincoln, Nebraska, USA). We first performed an A-C i curve on each leaf using the Dynamic Assimilation Technique (DAT) [25, 51, 52] in order to estimate rates of V cmax and J max . For each curve, CO 2 assimilation rates on a per leaf area basis ( A area ; μ mol CO 2 m -2 s -1 ) were logged every 4 seconds across continuously ramping CO 2 concentrations, with a ramp rate of 100 μ mol mol -1 min -1 [consistent with recommendations by 52, 53] beginning at 5 μ mol mol -1 CO 2 and concluding at 1700 μ mol mol -1 CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…First, V cmax , J max , and A max data were collected in the field using a LI-6800 Portable Photosynthesis System (Licor Bioscience, Lincoln, Nebraska, USA). We first performed an A-C i curve on each leaf using the Dynamic Assimilation Technique (DAT) [25, 51, 52] in order to estimate rates of V cmax and J max . For each curve, CO 2 assimilation rates on a per leaf area basis ( A area ; μ mol CO 2 m -2 s -1 ) were logged every 4 seconds across continuously ramping CO 2 concentrations, with a ramp rate of 100 μ mol mol -1 min -1 [consistent with recommendations by 52, 53] beginning at 5 μ mol mol -1 CO 2 and concluding at 1700 μ mol mol -1 CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This co-dependency means it is not truly possible to solve for f, but instead only for the relationship between f and b. For example, a recent comparison of tobacco and Rhazya stricta (Apocynaceae) found that f ranged from 10 to 30 ‰ but did not significantly differ between species (Gregory et al, 2023). However, this statistical comparison assumed b was constant.…”
Section: Fractionation Associated With Photorespiration (F)mentioning
confidence: 99%
“…'Sicot 71') and compare them with two published sets of parameters: one set from a tobacco study (Bernacchi et al, 2002) that is commonly used to define defaults in A/C i analysis routines, and one set from an antisense Rubisco small subunit (antirbcS) transgenic line of Arabidopsis (Walker et al, 2013). We assessed the impact of these different parameter sets on the modelled System Models (Booth et al, 2012;Matthews et al, 2007;Mercado et al, 2018;Rogers et al, 2017) and understanding the potential effects of modifying photosynthetic performance on crop productivity (Conaty & Constable, 2020;Gregory et al, 2023;Vijayakumar et al, 2023;Wu et al, 2019Wu et al, , 2023. photosynthesis.…”
Section: Introductionmentioning
confidence: 99%